Clinical and Endoscopic Response to Anti-Tumor Necrosis Factor-Alpha Antibody Therapy in a Patient With Cronkhite-Canada Syndrome - Roham Salman Roghani; Joline De Castro; Adewale B. Ajumobi (SAGE Publishing, 2023)
Cronkhite-Canada syndrome (CCS) is an acquired polyposis syndrome with gastrointestinal and extraintestinal manifestations. Given its rarity and lack of standard treatment, diagnosis and treatment are challenging. Steroid therapy and nutritional support are conventional treatments. There is no consensus on management of steroid-refractory cases. Here, we report the diagnosis and treatment course of a 54-year-old Asian male with CCS, whose initial treatment with prednisone 60 mg a day led to partial response and disease flare up during prednisone tapering. The use of infliximab and azathioprine led to promising remission of his symptoms.